WAVELET OSCILLATOR NEURAL NETWORKS FOR TEXTURE SEGMENTATION - Sengur, Abdulkadir; Turkoglu, Ibrahim; Ince, M. Cevdet (Acad Sciences Czech Republic, Inst Computer Science, 2008)
Texture can be defined as a local statistical pattern of texture primitives in observer's domain of interest. Texture analysis such as segmentation plays a critical role in machine vision and pattern recognition applications. The widely applied areas are industrial automation, biomedical image processing and remote sensing. This paper describes a novel system for texture segmentation. We call this system Wavelet Oscillator Neural Networks (WONN). The proposed system is composed of two parts. A second-order statistical wavelet co-occurrence features are the first part of the proposed system and an oscillator neural network is in the second part of the system. The performance of the proposed system is tested on various texture mosaic images. The results of the proposed system are found to be satisfactory.
Keywords: Wavelet decomposition; wavelet oscillator neural networks; texture segmentation; feature extraction